2008
DOI: 10.5194/angeo-26-1255-2008
|View full text |Cite
|
Sign up to set email alerts
|

Emerging pattern of global change in the upper atmosphere and ionosphere

Abstract: Abstract. In the upper atmosphere, greenhouse gases produce a cooling effect, instead of a warming effect. Increases in greenhouse gas concentrations are expected to induce substantial changes in the mesosphere, thermosphere, and ionosphere, including a thermal contraction of these layers. In this article we construct for the first time a pattern of the observed long-term global change in the upper atmosphere, based on trend studies of various parameters. The picture we obtain is qualitative, and contains seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 79 publications
(130 reference statements)
6
96
0
Order By: Relevance
“…The whole period is separated into two sub-periods (1957-1989 and 1990-2002). The sub-periods were chosen in accordance with the change in trends of yearly averaged winds in the mesopause region (Laštovička et al, 2008). The selected latitude of 52.5 • N is separated into four sectors (0-90 • E -European sector, 90-180 • E -Asian sector, 180-300 • W -Pacific-American sector, and 300-360 • E -Atlantic sector).…”
Section: Methodsmentioning
confidence: 99%
“…The whole period is separated into two sub-periods (1957-1989 and 1990-2002). The sub-periods were chosen in accordance with the change in trends of yearly averaged winds in the mesopause region (Laštovička et al, 2008). The selected latitude of 52.5 • N is separated into four sectors (0-90 • E -European sector, 90-180 • E -Asian sector, 180-300 • W -Pacific-American sector, and 300-360 • E -Atlantic sector).…”
Section: Methodsmentioning
confidence: 99%
“…They have shown that even under the double CO 2 increase scenario (which we are very far from) the predicted ionospheric effects should be small. But their results have stimulated researchers to relate the observed ionospheric long-term trends to the thermosphere greenhouse cooling (Ulich & Turunen, 1997;Sharma et al, 1999;Alfonsi et al, 2001Alfonsi et al, , 2002La stovička et al, 2008;Qian et al, 2008Qian et al, , 2009La stovička et al, 2012;Danilov & Konstantinova, 2013;Mielich & Bremer, 2013;Konstantinova & Danilov, 2015;Roininen et al, 2015). The mechanisms of the thermospheric and ionospheric trends may be different and serious contradictions with the CO 2 hypothesis confirm this (Perrone & Mikhailov, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The cycles of the variations in electron density are in agreement with each wave cycle. However, clear long-term variations in atmospheric wave activity have not been obtained [e.g., Gavrilov et al, 2002;Jacobi et al, 2006;Laštovička et al, 2008]. Thus, it is not likely that atmospheric waves cause the longterm variations in tweek reflection height.…”
Section: Comparison With Empirical Modelsmentioning
confidence: 99%